Generalized Phase Contrast: Applications in Optics and Photonics - Glückstad, Jesper; Palima, Darwin (Springer Series in Optical Sciences, 2009)
Generalized Phase Contrast elevates the phase contrast technique not only to improve phase imaging but also to cross over and interface with diverse and seemingly disparate fields of contemporary optics and photonics. This book presents a comprehensive introduction to the Generalized Phase Contrast (GPC) method including an overview of the range of current and potential applications of GPC in wavefront sensing and phase imaging, structured laser illumination and image projection, optical trapping and manipulation, and optical encryption and decryption. The GPC method goes further than the restrictive assumptions of conventional Zernike phase contrast analysis and achieves an expanded range of validity beyond weak phase perturbations. The generalized analysis yields design criteria for tuning experimental parameters to achieve optimal performance in terms of accuracy, fidelity and light efficiency. Optimization can address practical issues, such as finding an optimal spatial filter for the chosen application, and can even enable a Reverse Phase Contrast mode where intensity patterns are converted into a phase modulation. Audience Researchers and graduate students in optical sciences, particularly those interested in the novel applications of optical sensing and modulation techniques in contemporary optics and photonics.